Antihypertensive effects of Korean wild simulated ginseng (Sanyangsam) extracts in spontaneously hypertensive rats - Moon, Jae-Nam (Food Sci Biotechnol, 2019)
Ginseng possesses a wide spectrum of medicinal effects and has widely been used in traditional medicine for thousands of years. In this study, the antihypertensive effect of Korean wild simulated ginseng in spontaneously hypertensive rats was investigated. Three groups of hypertensive rats—a group without wild simulated ginseng treatment; another group treated with 100 mg of wild simulated ginseng extract/kg of body weight; and the other group treated with 200 mg of wild simulated ginseng extract/kg of body weight were tested over 8 weeks. The two wild simulated ginseng-treated groups showed significantly (p < 0.05) reduced systolic blood pressure at 4 and 6 weeks of wild simulated ginseng treatment. However, the wild simulated ginseng treatment did not adversely affect the food intake, serum electrolytes, osmolality, heart weight, heart rate, and the cross-section of the aorta as well as enzyme activities. The results suggested that Korean wild simulated ginseng is effectively used for reducing high systolic blood pressure in hypertensive patients without causing adverse health effects.